Administração epidural de tiletamina-zolazepam ou da associação de romifidina e morfina em eqüinos - Paes, Simone Dias de Lima Alves (2002)
Epidural analgesia has been used as an adjuvant to general anesthesia, being an effective procedure to treat the acute and cronic pain. This tecnique allow preoperative, transoperative and postoperative analgesia. Three drugs were studied to evaluate the cardiovascular and respiratory function, sedation, analgesia and behavior. All horses received 0,5 and 1,0mg/kg tiletamine-zolazepam and no cardiovascular or respiratory changes were detected. Although there was no sedation, some horses showed ataxia and analgesia was considered moderate. Epidural tiletamine-zolazepam does not produce cardiac or respiratory depression, producing moderate analgesia and ataxia. The epidural administration of morphine and romifidine (T30 - 0,1mg/kg morphine and 30mcg/kg romifidine and T60 - 0,1mg/kg morphine and 60mcg/kg romifidine) reduces cardiac and respiratory rate and produces sedation. There was no respiratory depression or hypotension and in treatment T60 analgesia lasted longer than in treatment T30. The epidural administration of morphine and romifidine combination produces moderate analgesia with prolonged effect when 60mcg/kg romifidine is used. There is profound sedation and neither cardiac or respiratory depression nor cardiac arrhythmia were observed.